Measuring E-Commerce Customer Satisfaction and Loyalty in Jakarta Using E-SERVQUAL and IPA Case Study JD.ID - Islam, Sri Susilawati; Redi, Anak Agung Ngurah Perwira; Lestari, Tika Endah; Prasetyo, Yogi Tri; Effendi, Nabila Salsabillah; Young, Michael Nayat (Faculty of Engineering and Technology, Sampoerna University, 2025)
In order to improve customer satisfaction and loyalty to e-commerce, certain aspects of e-service quality need to be emphasized. To evaluate the collected data, the study employs SEM-PLS, and Importance Performance Map Analysis (IPA). The findings show that variables such as website reliability, security, compensation, responsiveness, personalization, and assurance significantly affect consumer satisfaction, which in turn has a positive influence on customer loyalty. According to the results of the IPA research, e-commerce must concentrate on security factors which have 0.086 importance to strengthen its security controls and increase customer loyalty and trust. Hence, to maintain high-priority variables, e-commerce should also maintain website design variables and customer satisfaction.